Do courts matter for firm value? Evidence from the U.S. court system - Stefano Colonnello; Christoph Herpfer (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2018)
We estimate the impact of U.S. state court characteristics on firm value by exploiting a U.S. Supreme Court ruling that exogenously changed firms` exposure to different courts. We find that increased exposure to more business-friendly courts is associated with positive announcement returns. We find no such association for objective court quality. We confirm that this U.S. Supreme Court ruling impacted firm value through the legal environment channel. We show that this ruling reduced the ability of affected firms to remove cases from certain state courts, and we show that announcement returns are stronger for firms that have high litigation exposure.
Keywords: G32; G34; G38; K40; 330; courts; litigation; governance